PEMBERDAYAAN MASYARAKAT MELALUI TEKNOLOGI CO-COMPOST BIOCHAR SEBAGAI ALTERNATIF PUPUK ORGANIK PADA TANAMAN PADI DI KELOMPOK ABDI TANI KECAMATAN KAKAP KABUPATEN KUBU RAYA - Suci, Ida Ayu; Bancin, Hardi Dominikus; Muliani, Muliani (Universitas Mataram, 2025)
The Abdi Tani Farmers Group in Sungai Itik Village, Sungai Kakap District, Kubu Raya Regency, faces the problem of low quality acid sulfate soil and dependence on synthetic chemical fertilizers, so that rice productivity is not optimal. One solution offered is the use of biochar co-compost technology, a combination of rice husk biochar and water hyacinth compost that functions as an organic fertilizer and soil conditioner. This technology can increase soil pH, reduce the impact of pyrite toxicity, improve soil structure, and increase nutrient availability for plants. This Community Service Activity aims to increase the capacity of farmers in producing and applying biochar co-compost, as well as strengthening aspects of economic independence through marketing biochar co-compost products. The activity method includes observation, planning, implementation, application, and evaluation of activities. Knowledge evaluation is carried out through pre-tests and post-tests, while skill improvements are observed through direct practice. The activities carried out were training in making organic compost from water hyacinth, training in co-compost biochar technology, application of co-compost biochar in rice fields, packaging and branding of co-compost biochar products, as well as offline and online product marketing for co-compost biochar products. The results of the activity showed that participants' knowledge increased significantly, as evidenced by their high post-test scores. The Abdi Tani Farmers Group successfully produced biochar co-compost independently and applied it to rice paddies. Field observations showed improvements in soil physical condition and increased plant vigor after application. Furthermore, assistance with packaging, branding, and marketing resulted in packaged biochar co-compost products that began to be marketed locally and digitally. Biochar co-compost technology effectively improves soil quality and rice growth while strengthening the independence and economic capacity of farmer groups